Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

See more answers at brainly.com

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

7x-9y=4 => slope = 7/9
the equation of the line will be
y=mx+b
-6=(7/9)*7+b
and then solve for b

im still confuse with this..

which step?

the line is parallel to the given line, so it has the same slope

how would i write the equation for Y=

hi, first before we get the parallel line equation,:
from this equation
7x-9y=4 what is y=?

y= 7/9x-4/9

ok good with this line y= 7/9x-4/9 what is your slope m=?

@ MauriceLong
did you get it ?

the slope is 4

ok

can u help me solve this problem please

ok. i am getting a better understanding on this so far.

from
y= mx + b
y= 7/9x - 4/9 what is the slope m?

yesss just answer what i ask you and you will get it ... :D

try to compare the formula to the one you answered on y=7/9 x -4/9

would i have too subtract 7/9-4/9

ok

|dw:1354520274544:dw|

im having a hard time solving this problem

ok i will show you the easy way of doing the solution of it,,, :D

ok

we want to know the slope m of this particular line
|dw:1354578182118:dw|

from
y= mx + b
y= 7/9x + - 4/9 we know that b=-4/9,, what is slope m=?

I dont know how too get the slope. Confuse.

do i subtract -4/9 too both sides

so the slope is 4/9

from
y= mx + b
y= 7/9x + - 4/9
that is b=-4/9,, what is m?

m=7/9

yessss : correct :D

y-y1=7/9(x-x1)

7x-6y

this is what you said the answer y-y1=7/9(x-x1)
all you need to do is to sub what is x1 and y1 there

(x1,y1)=(7,-6); sub this to your answer y-y1=7/9(x-x1)

if you have a point of (7,-6) your x1=7 and y1=-6... therefore
this can be like this
(x1,y1)=(7,-6)

therefore plug those x1 =7 and y1=-6 to your answer y-y1=7/9(x-x1)

y=7/9(x-6)

y - y1 = 7/9 ( x - x1 )
y - ____ = 7/9 (x - ______)

y-6=7/9(x-7)

your answer
y-6=7/9(x-7)
-6 is not correct because y- -6=__?

y - y1 = 7/9 ( x - x1 )
y - -6 = 7/9 (x - 7) try to simplify this more